Comparison of Computed Tomography and 57Co-Bleomycin Scintigraphy in Staging the Mediastinal Lymph Nodes of Patients with Non-Small-Cell Lung Cancer - van der Laan, J. G.; van den Brink, A.; de Boer, W. J.; Piers, D. A.; Beekhuis, H.; Kengen, R. A. (Nuklearmedizin - NuclearMedicine, 1990)
The value of computed tomography (CT) and of 57Co-bleomycin scintigraphy (57Co-BLM) in staging the mediastinal lymph nodes was compared in 28 patients suffering from non-small-cell lung cancer. The results were assessed against the pathological findings obtained during thoracotomy or mediastinoscopy. CT staging of the mediastinum had a sensitivity of 75%, a specificity of 80%, an accuracy of 79%, a positive predictive index of 60% and a negative predictive index of 89%. 57Co-BLM scintigraphic staging had a sensitivity of 43%, a specificity of 94%, an accuracy of 80%, a positive predicitive index of 75% and a negative predictive index of 81 %. In this small series these differences were not statistically significant; it thus appears that CT and 57Co-BLM are of equal value in staging the mediastinum. Mediastinoscopy is not contributory in case of a negative CT or 57Co-BLM. A positive CT or 57Co-BIM, however, indicates the need for histological verification of the mediastinal findings.Es wurde der Wert der Computertomographie (CT) und der Szintigraphie mit 57Co beim Staging mediastinaler Lymphknoten bei 28 Patienten mit nichtkleinzelligen Bronchialkarzinomen festgestellt und mit den Befunden aus Thorakotomie oder Mediastinoskopie verglichen. Die Sensitivität der Computertomographie beim mediastinalen Staging betrug 75%, die Spezifität 80% und die Treffsicherheit 79%. Der positive Vorhersageindex war 60, der negative 89%. Die Sensitivität der Szintigraphie betrug 43%, die Spezifität 94 und die Treffsicherheit 80%. Der positive Vorhersage-index war 75%, der negative 81%. Bei dieser relativ kleinen Untersuchungsreihe fand sich keine statistisch signifikante Differenz; CT und 57Co-BLM sind für das Staging des Mediastinums offenbar gleichwertig. Die Mediastinoskopie ist bei negativem CT oder 57Co-BLM-Befund nicht weiterführend. Im Falle eines positiven CT oder 57Co-BLM-Befundes erscheint jedoch eine histologische Verifikation des mediastinalen Befundes angezeigt.